Court Competence In Administration In Resolving The Land Disputes To The Land - Siti Fatimah Nur Afifah; Zubaida Djaiz Baranyanan; M. Zamroni; Bambang Panji Gunawan (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
The purpose of this study is to describe the competence of the State Administrative Court in handling land disputes. With the existence of a duplicate certificate of ownership originating from two legal aspects there is also a dualism in handling the case, and with the existence of the antinomy of this legal norm, this can further lead to a conflict of competence in adjudicating between the General Court or State Administrative Court in resolving land disputes. This research uses a normative method, in which the sources of legal materials are used by using literature studies, legislation, journals / articles, jurisprudence and books. Significantly this research shows that the competency of Administrative Court becomes a place that should be a reference for legal certainty seekers for the existence of a double certificate that can be tested for validity through the State Administrative Court for the Decree of a State Administration officia.